Letter to the editor: Analysis of stroke patient migration for mechanical thrombectomy and changes in neurointerventional center size in Germany - Weber, Ralph; Bartig, Dirk; Krogias, Christos; Richter, Daniel; Hacke, Werner; Eyding, Jens (Neurological research and practice, 2021)
AIM AND METHODS: To analyse nationwide changes in neurointerventional center size of all German hospitals performing mechanical thrombectomy (MT) in stroke patients from 2016 to 2019. Furthermore, we assessed cross-district patient migration for MT for the first time using hospitals' structured quality reports and German Diagnosis-Related Groups data in 2019. FINDINGS: Number of hospitals performing more than 100 MT procedures/year doubled in Germany from 2016 (n = 36) to 2019 (n = 71), and these neurointerventional centers performed 71% of all MT procedures in 2019. The overall increase in MT procedures was largely driven by these high-volume neurointerventional centers with ability to perform MT 24/7 (121% increase as compared with 8% increase in hospitals performing less than 100 MT procedures/year). The highest cross-district patient mobility/transfer of stroke patients for MT was observed in districts adjacent to these high-volume neurointerventional centers with existing neurovascular networks. CONCLUSION: The substantial increase in MT procedures observed in Germany between 2016 and 2019 was almost exclusively delivered by high-volume stroke centers performing more than 100 MT procedures per year in established neurovascular networks. As there is still a reasonable number of districts with low MT rates, further structural improvement including implementation of new or expansion of existing neurovascular networks and regional tailored MT triage concepts is needed.
Gesehen am 09.06.2021